Infections - Message, Simon D. (Asthma and COPD, 2009)
This chapter reviews the epidemiological evidence implicating infectious pathogens as triggers and will discuss the mechanisms of interaction between the host–pathogen response and preexisting airway pathology that result in an exacerbation. Asthma is a multifaceted syndrome involving atopy, bronchial hyperreactivity, and IgE and non-IgE-mediated acute and chronic immune responses. The asthmatic airway is characterized by an infiltrate of eosinophils and of T-lymphocytes expressing the type 2 cytokines IL-4, IL-5, and IL-13. Trigger factors associated with acute exacerbations of asthma include exposure to environmental allergens, especially animals, molds, pollens and mites, cold, exercise, and drugs. The frequency of exacerbations is a major factor in the quality of life of patients with COPD. The typical clinical features of an exacerbation include increased dyspnea, wheezing, cough, sputum production, and worsened gas exchange. Although noninfectious causes of exacerbations such as allergy, air pollution, or inhaled irritants including cigarette smoke may be important, acute airway infections are the major precipitants. The infection and consequent host inflammatory response result in increased airway obstruction. The success of vaccination to prevent respiratory virus infections has been limited by significant variation within the major virus types causing disease. Currently much of the treatment of infective exacerbations of asthma and COPD is symptomatic, consisting of increased bronchodilators, either short-acting β 2—agonists in inhaled or intravenous form or anticholinergics or theophyllines, or supportive in the form of oxygen and in severe cases noninvasive or invasive ventilatory measures.